Transcriptome analysis of pterygium and pinguecula reveals evidence of genomic instability associated with chronic inflammation - Suarez, María Fernanda (2021)
Solar damage due to ultraviolet radiation (UVR) is implicated in the development of two proliferative lesions of the ocular surface: pterygium and pinguecula. Pterygium and pinguecula specimens were collected, along with adjacent healthy conjunctiva specimens. RNA was extracted and sequenced. Pairwise comparisons were made of differentially expressed genes (DEGs). Computational methods were used for analysis. Transcripts from 18,630 genes were identified. Comparison of two subgroups of pterygium specimens uncovered evidence of genomic instability associated with inflammation and the immune response; these changes were also observed in pinguecula, but to a lesser extent. Among the top DEGs were four genes encoding tumor suppressors that were downregulated in pterygium: C10orf90, RARRES1, DMBT1 and SCGB3A1; C10orf90 and RARRES1 were also downregulated in pinguecula. Ingenuity Pathway Analysis overwhelmingly linked DEGs to cancer for both lesions; however, both lesions are clearly still benign, as evidenced by the expression of other genes indicating their well‐differentiated and non‐invasive character. Pathways for epithelial cell proliferation were identified that distinguish the two lesions, as well as genes encoding specific pathway components. Upregulated DEGs common to both lesions, including KRT9 and TRPV3, provide a further insight into pathophysiology. Our findings suggest that pterygium and pinguecula, while benign lesions, are both on the pathological pathway towards neoplastic trans-formation.